Improved stabilisation design for networked control systems with compound Markovian transition probabilities. (27th November 2012) - Hui, Guotao; Liu, Yisheng; Wang, Yingchun
This paper is concerned with the stabilisation design problem of Networked Control Systems (NCSs) with a compound Markovian transition probabilities. For handling the inter–sample behaviour, a novel segmented norm bounded method is proposed. By using this method, the conservativeness which is related to the larger interval of network–induced delay can be reduced. Correspondingly, a less conservative mode dependent stabilisation criterion expressed in terms of linear matrix inequalities is obtained. The effectiveness and merits of the proposed method are finally illustrated via numerical simulation.